2000
DOI: 10.1111/j.1528-1157.2000.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Single Seizure on Health Status and Health Care Utilization

Abstract: Summary:Purpose: To assess the health status of patients after a single seizure.Methods: We compared single-seizure patients (SS) with patients who had well-controlled epilepsy (WC), and uncomplicated hypertension (HT). Patients were adults screened from emergency and outpatient units of two urban teaching hospitals using predefined criteria. The 83 patients (SS, 30; WC, 29; HT, 24) were interviewed by phone about functional status (SF-36), comorbid illness, cause of illness, number of visits to health provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Previous cross‐sectional studies (18–20,23) had shown that subscales of the SF‐36 are valid in respect to patient groups with different seizure frequencies and with or without side effects of AEDs. Compared with the German reference population, the participants in our study had significantly (p < 0.01) lower (0, worst; 100, best) scores on the SF‐36, especially on physical role functioning (women, 67.8 vs. 80.4; men, 68.0 vs. 87.3), vitality (women, 47.0 vs. 60.6; men, 53.9 vs. 66.2), social functioning (women, 72.4 vs. 87.0; men, 75.2 vs. 90.1), emotional role functioning (women, 64.6 vs. 92.1; men, 69.3 vs. 92.1), and mental health (women, 59.8 vs. 76.6; men, 64.0 vs. 76.6) at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross‐sectional studies (18–20,23) had shown that subscales of the SF‐36 are valid in respect to patient groups with different seizure frequencies and with or without side effects of AEDs. Compared with the German reference population, the participants in our study had significantly (p < 0.01) lower (0, worst; 100, best) scores on the SF‐36, especially on physical role functioning (women, 67.8 vs. 80.4; men, 68.0 vs. 87.3), vitality (women, 47.0 vs. 60.6; men, 53.9 vs. 66.2), social functioning (women, 72.4 vs. 87.0; men, 75.2 vs. 90.1), emotional role functioning (women, 64.6 vs. 92.1; men, 69.3 vs. 92.1), and mental health (women, 59.8 vs. 76.6; men, 64.0 vs. 76.6) at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in control, physical injury, and prolonged postictal symptoms can lead to loss of confidence and impairment of independence. Longer‐term sequelae include employment difficulties, rescinding of the driving license, worry about having further events, and changes in attitude among family and friends (Dworetzky et al, 2000). Indeed, Lindsten and colleagues recently reported that adults with a newly diagnosed unprovoked epileptic seizure became significantly less physically active, traveled abroad less frequently, and were generally less energetic during their leisure time than sex‐ and age‐matched referents (Lindsten et al, 2003).…”
mentioning
confidence: 99%
“…In the present study, we report that cortical excitability is increased in patients who presented with an isolated seizure with no history of recurrence for at least three (3)(4)(5)(6) years. This increase occurs in a pattern similar to that observed in patients in epilepsy but is of a smaller magnitude.…”
Section: Discussionmentioning
confidence: 47%
“…3 The diagnosis of epilepsy will have a profound psychosocial effect on those patients including employment difficulties, rescinding of the driving license and changes in attitude among family and friends. 4 It also entails initiation of anti-epileptic drug (AED) therapy and coping with the many side effects associated with that. 5 For this reason, many epidemiological-and population-based studies have examined the risk of seizure recurrence after a first seizure.…”
Section: Introductionmentioning
confidence: 99%